Propuesta de un programa de relaciones públicas para mejorar la atención al cliente externo de la Municipalidad Distrital de Olmos 2015 - Morales Gutierrez, María Edith (2019)
ABSTRACT Every organization is based on its clients and it is them who qualify the kind of attention that is offered to them, expressing their rights or mistakes of those who attended them, qualifying it as excellent or terrible. An excellent customer service or terrible customer service can lead not only to the closeness or distancing of this, but also to the deterioration of the good image of the organization. Therefore, the objective of this research is to offer a proposal of a Public Relations program that contributes to improve the attention provided to the clients of the District Municipality of Olmos, for which it was necessary to make a diagnosis of the reality of the institution to determine the actions to take and to implement towards the achievement of the objectives. 169 people were surveyed (external clients) who come to the municipality to request a service, sample obtained from the daily attention report. The design used in this research is the non-experimental, cross-sectional description. The survey technique was used which allowed us to identify the strengths and weaknesses of the agents involved, problems and difficulties that arise from attention provided. The analytical and statistical method was used, taking as a result that the attention in the institution is very bad according to the tables and figures described, being one of the most outstanding conclusions that the lack of motivation of the workers whose actions damage the good attention that should be provided to the external client, in this sense it is necessary to propose a program that allows to meet the multiple needs and welfare of employees by strengthening their skills in such a way that contributes to an improvement in the attention to external customers, generating positive perceptions about the public entity by providing more effective and more efficient care and therefore also those contribute to strengthen and enhance the institutional image.